STUDYPATIENT WITHHEPATITISB(HBsAg) POSITIVE(+) ON THERELATIONSHIPBETWEENINDIVIDUALIN THE FAMILY - Jiwintarum, Yunan; Getas, I Wayan; Marnia, Marnia (Jurnal Analis Medika Biosains (JAMBS), 2014)
Abstrak Hepatitis B is a disease caused by Hepatitis B. Hepatitis B virus can cause acute orchronicillness, and hepatitis can progress to cirrhosis and primary liver carcinoma. The purpose of this study was to determinethe occurrence of HBsAg Positive(+) on the relationship between individuals in the family. This study is the observation that laboratory research conducted by observation through laboratory tests and Non-Random sampling with purposive sampling technique.The results of examination of HBsAg inpatients with hepatitis B family members found 4 people(8.33%) HBsAg positive(+) and 44(91.67%) of HBsAg negative (-) of 48 people were examined.Keywords: Positive HBsAg(+), Family, Patients with HepatitisB